The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1681/asn.2022010125
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transcriptomes of SARS-CoV-2–Infected Kidney Transplant Recipients Associated with Immune Insufficiency Proportionate to Severity

Abstract: BackgroundAmong patients with COVID-19, kidney transplant recipients (KTRs) have poor outcomes compared with non-KTRs. To provide insight into management of immunosuppression during acute illness, we studied immune signatures from the peripheral blood during and after COVID-19 infection from a multicenter KTR cohort.MethodsWe ascertained clinical data by chart review. A single sample of blood was collected for transcriptome analysis. Total RNA was poly-A selected and RNA was sequenced to evaluate transcriptome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These will serve as biomarkers indicating treatment responsiveness. 61 , 62 , 64 , 68 Biomarkers identified at baseline can enrich participation, help risk stratification, whereas those that associate with treatment responsiveness can reduce duration or costs in subsequent FSGS trials. 64 , 69 , 70 …”
Section: Study Outcomesmentioning
confidence: 99%
“…These will serve as biomarkers indicating treatment responsiveness. 61 , 62 , 64 , 68 Biomarkers identified at baseline can enrich participation, help risk stratification, whereas those that associate with treatment responsiveness can reduce duration or costs in subsequent FSGS trials. 64 , 69 , 70 …”
Section: Study Outcomesmentioning
confidence: 99%
“…Decreased immunosuppression is generally not associated with increased rejection. In a study of 64 KTRs with COVID-19, 31 with acute COVID-19 (<4 weeks from diagnosis) and 33 with post-acute COVID-19 (>4 weeks postdiagnosis) blood transcriptomes were examined ( 60 ). The authors reported upregulation of neutrophil and innate immune pathways but downregulation of T cell and adaptive immune activation pathways with acute infection.…”
Section: Other Immunosuppression Considerationsmentioning
confidence: 99%
“…First, the comparison of hospitalized patients during different epidemic waves is subject to several confounding and historical biases, including the use of corticosteroids and anti-IL-6 antagonists (i.e., tocilizumab), and evolution of the clinical context, notably the increasing role of immunodepression in the severity of the disease 12. Furthermore, previous transcriptomicsbased studies highlighted the impact of vaccination and immunosuppression on the immune response of COVID-19 patients [46][47][48]. However, the unsupervised analysis of the entire cohort did not show any impact of the immunocompromised or vaccinated status on the distribution of the transcriptomic data.…”
mentioning
confidence: 99%